Maternal high-fat diet increases independent feeding in pre-weanling rat pups - Kojima, Sayuri (Physiol Behav, 2016)
In laboratory settings, the adult offspring of rodent dams that are maintained on high-fat diet (HFD) before conception and/or during pregnancy/lactation display an increased incidence of obese phenotypic markers, including increased body weight and adiposity, reduced leptin sensitivity, and impaired glucose tolerance. In rat pups raised by dams consuming HFD, these obese markers emerge during the first postnatal week. Since the week-old offspring of HFD dams consume excess amounts of milk during experimental tests of independent feeding (i.e., intake away from the dam), we hypothesized that maternal diet affects suckling and/or independent ingestion by pups in the home-cage environment. In the present study, this hypothesis was tested by conducting detailed analyses of ingestive behaviors expressed by pups in the home cage. Pups raised by dams consuming HFD displayed an earlier onset of independent feeding and more amounts of calorie intake from solid food during the third postnatal week compared to pups raised by dams consuming regular chow, with no diet-related differences in suckling behavior. Independent ingestion by pups in both diet groups was most frequently observed after nursing, with offspring of HFD dams engaged more frequently in post-nursing independent feeding episodes compared to offspring of chow-fed dams, particularly when the prior nursing episode was nutritive (i.e., including milk receipt by pups). We conclude that early-life exposure to HFD enhances the facilitative effect of nutritive suckling on independent feeding in pups, promoting increased caloric intake from solid food in the home-cage environment.